Stump's Forgiveness - Warmke, Brandon (2019)
To love someone, Eleonore Stump tells us, is to have two desires: a desire her objective good and a desire for union with her. In Atonement, Stump claims that loving someone-understood as having these desires-is necessary and sufficient for morally appropriate forgiveness. I offer several arguments against this claim.
Keywords: Forgiveness; Atonement; Repentance; Satisfaction